Teaching Statistics in School Mathematics-Challenges for Teaching and Teacher Education
XVII, 425 p.
Keywords: In recent years, there have been an expansion and renewal of the statistics content in the mathematics curricula in many countries through all school grade levels from primary to secondary levels. However, no similar attention has been paid to the preparation of mathematics teacher to teach statistics at these levels. This book presents the results from the Joint ICMI/IASE Study, Teaching Statistics in School Mathematics. Challenges for Teaching and Teacher Education that was intended to address the lack of attention to teaching statistics by promoting international collaborative research specifically focussed on the education and professional development of teachers to teach statistics.The volume covers a very wide field, including examples of statistics curricula and teacher education programmes around the world; analysis of the fundamentals to teaching statistics; survey chapters of research related to teachers’ attitudes, beliefs and knowledge related to fundamental statistics ideas and its teaching; and analyses of challenges and experiences related to training teachers to teach statistics. The book is designed to be useful to researchers in mathematics education and statistics education teacher educators, and people involved in curricular development in statistics with the hope that it will foster further research in the problems related to educating teachers to teach statistics at different school levels. It could be of interest to teachers themselves, since the basic ideas for teaching statistics and the research summarised in the book both in learning difficulties or teaching strategies is applicable in both the training of students and teachers. .